2006
DOI: 10.1177/1049731505282593
|View full text |Cite
|
Sign up to set email alerts
|

Housing First Services for People Who Are Homeless With Co-Occurring Serious Mental Illness and Substance Abuse

Abstract: The literature on homeless adults with severe mental illness is generally silent on a critical issue surrounding service delivery—the contrast between housing first and treatment first program philosophies. This study draws on data from a longitudinal experiment contrasting a housing first program (which offers immediate permanent housing without requiring treatment compliance or abstinence) and treatment first (standard care) programs for 225 adults who were homeless with mental illness in New York City. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
218
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(250 citation statements)
references
References 36 publications
5
218
0
6
Order By: Relevance
“…Missing values for any of these items were replaced by the mean value for that specific item PTSD post-traumatic stress disorder daily substance use in our study (29 %) is dramatically higher than other Housing First intervention studies of homeless, mentally ill persons. 2,7 In previous studies, drug use was characterized as high frequency when the participant reported using 4 days out of the past 6 months (G25 %) and heavy alcohol use consisted of consuming alcohol on 28 days out of the past 6 months 7 or 15 days in the previous month (16 %). 2 As with the high-frequency substance users in the Collaborative Initiative on Chronic Homelessness study, 2 DSUs in our sample also experienced long durations of homelessness over their lifetime and had more mental health symptoms compared to participants who were abstinent or used substances less than daily.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Missing values for any of these items were replaced by the mean value for that specific item PTSD post-traumatic stress disorder daily substance use in our study (29 %) is dramatically higher than other Housing First intervention studies of homeless, mentally ill persons. 2,7 In previous studies, drug use was characterized as high frequency when the participant reported using 4 days out of the past 6 months (G25 %) and heavy alcohol use consisted of consuming alcohol on 28 days out of the past 6 months 7 or 15 days in the previous month (16 %). 2 As with the high-frequency substance users in the Collaborative Initiative on Chronic Homelessness study, 2 DSUs in our sample also experienced long durations of homelessness over their lifetime and had more mental health symptoms compared to participants who were abstinent or used substances less than daily.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently, Housing First has been shown to be effective among homeless individuals with active substance use disorders. 2,7 However, while substance use per se was prevalent among participants in these studies, the implications of different severities and forms of substance use have not been well characterized in this context. For example, Padgett et al 7 defined heavy use of drugs as using 4 days out of the previous 6 months.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The NYHS was a four-year trial in which homeless mentally ill adults received immediate housing through Pathways (the experimental condition) or 'usual care' ('treatment first') and were assessed for an array of outcomes (Tsemberis, Gulcur & Nakae, 2004). Quantitative findings from the NYHS revealed significantly greater housing stability among the experimental group members enrolled in Pathways (Padgett, Gulcur & Tsemberis, 2006;Tsemberis et al, 2004). …”
Section: From a Randomized Experiments To A 'Natural' Experiment: The mentioning
confidence: 99%
“…Dans deux des trois études qui ont comparé l'approche « logement d'abord » avec les interventions psychosociales traditionnelles, les personnes qui ont eu accès à un programme basé sur l'approche « logement d'abord » ont passé moins de temps en situation d'itinérance et plus de temps dans un logement que celles qui ont fait l'objet d'interventions psychosociales traditionnelles (tableau 8) (Montgomery et al, 2013 ;Padgett, Gulcur & Tsemberis, 2006). Ces résultats sont aussi rapportés dans les revues systématiques de Nelson et al (2007) et Rog (2004.…”
Section: Comparaison Entre L'approche « Logement D'abord » Et Les Intunclassified